Pengaruh Atensi Pendidik dalam Penguasaan TI dari IPTEK Pendidik dan Lingkungan Sekolah terhadap Kompetensi Profesional selama Pandemi di SMKN 11 Malang - Dimas Ferry Kurniawan; Satrio Hadi Wijoyo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Covid-19 pandemic has had an impact on education in Indonesia. Educators in fulfilling obligations during the pandemic must provide knowledge to students online. Technological developments are increasingly advanced, especially in the field of education. During the pandemic, educators can provide online learning, for professional skills regarding information technology are needed. In improving professional competence, educators must attend workshops or seminars. This study aims to determine the attention of educators in mastering IT during the Covid-19 pandemic. Combination research is a mixture of both quantitative and qualitative methods. The research subjects used were all educators at SMKN 11 Malang with a total population and sample of 86 respondents using questionnaires and interviews as data collection tools. The results of the t-test for the science and technology variable affect professional competence, the school environment variable affects the professional competence of educators. Then for the F test, the variables of science and technology and the school environment have a simultaneous effect on professional competence. The value of R square for the science and technology variable of educators has an effect of 25.1% on professional competence, then for the school environment variable, it has an effect of 41.1% on professional competence. As for the two variables, namely the science and technology variable and the school environment, the effect is 45.2% simultaneously. Then the rest is influenced by other factors. The results of the questionnaire were also supported by interviews with 8 educators who said that IT mastery can be seen from the variables of science and technology and the school environment affecting professional competence. Therefore, the results of the interviews were strengthened from the results of the questionnaire and expanded by providing other factors that impacted the mastery of IT educators at SMKN 11 Malang.